Taking Hold of the Real : Dietrich Bonhoeffer and the Profound Worldliness of Christianity. - Harvey, Barry, 1954- (Wipf and Stock Publishers, 2015)
Dietrich Bonhoeffer writes in one of his last prison letters that he had ""come to know and understand more and more the profound this-worldliness of Christianity."" In Taking Hold of the Real, Barry Harvey engages in constructive conversation with Bonhoeffer, contending that the ""shallow and banal this-worldliness"" of modern society is ordered to a significant degree around the social technologies of religion, culture, and race. These mechanisms displace human beings from their traditional connections with particular locales, and relocate them in their ""proper places"" as determined by the.